INFLUENCE OF THE PRESENCE OF CROTAMINE IN THE COMPOSITION OF THE CROTALUS DURISSUS TERRIFICUS VENOM FACE TO CROTALIC ANTIVENOM, A HISTOLOGICAL APPROACH - Silva, Fâni Ribeiro; Cantuária, Nathalia Margarida; de Azevedo, Jonas Eligio Garcia; dos Santos, Gabriel Ferreira; de Souza, Jocimar; Calderon, Leonardo da Silva Rodrigues; Ravazoli, Isabella; Cogo, José Carlos; Floriano, Rafael Stuani; Hyslop, Stephen; Oshima-Franco, Yoko (Seven Editora, 2026)
The main fractions isolated from Crotalus durissus terrificus venom include crotamine, gyrotoxin, crotoxin, convulxin and phospholipase A2. The antivenom is produced by a pool from Crotalus durissus ssp venoms, which do not always express crotamine, which may reflect on the treatment. The objective was to evaluate, by light microscopy, the effectiveness of antivenom in cellular injuries induced by C. d. terrificus venom with (Vcrot+) and without (Vcrot-) crotamine. The study design was in vitro using routine histological procedures on donated neuromuscular preparations under Ethics Committee 201/2021, exposed to 1) control; 2) Vcrot+; 3) Vcrot-; and treated with antivenom in 4) preincubation and 5) post-venom models. The results were myotoxicity index (MI) in control preparations of 42.2 % ± 2.6 cells; Vcrot+ 95.2 % ± 1.8; Vcrot- 89.6 % ± 2.3. In the preincubation model, the antivenom significantly decreased the lesions to 74.1 % ± 3.8 of Vcrot+ and 71.9 % ± 4.5 of Vcrot-. In the post-venom model, the results were Vcrot+ ® 10’, 98.0 % ± 0.1; ® 30’, 84.8 % ± 0.1; and ® 60’ 85.6 % ± 0.1, while for Vcrot- were 84.7 % ± 0.1; 83.6 % ± 0.01 and 91.9 % ± 0.09, respectively. In conclusion, the antivenom neutralizes a major amount of constituents in the venom in the preincubation model, while in the post-venom model, it was not able against the myotoxic effects of both venoms, but allowed to show the sequence of pathological events in an ex vivo model.